A study on information skills in Portugal: Information Literacy and the European Higher Education Area (some global results) - Manuela Pinto (2010)
At the dawn of the 21st century, Portugal faces substantial social challenges. An expanding and increasingly complex Information Era requires citizens who are prepared and capable of facing the challenge of a competitive and globalized economy, where the use of and access to information and communication technologies assume a dominant position. The tasks of attending to the demands of this new model of social relationships have highlighted the absence of a consolidated social answer. Despite the fact that Portugal has been showing indicators of significant increases of digital inclusion, a digital divide is still present and difficult to overcome, because the inclusion of citizens regarding access to and the use of ICT is not proportional to the development of cognitive competences and abilities, as well as a critical evaluation, selection and use of information. In Portugal, only in the 1980s was it possible to initiate the implementation of a network of Public Libraries, which represents a serious delay in facing the challenging situation described earlier. This paper presents the results of a research project, supported by the FCT, which assess the level of information skills of Portuguese students in Higher and Secondary Education. The assessment intends to evaluate the level of preparation presented by the students to face not only the challenges of the "Network Society" but also the incoming changes of a European Higher Education Area.